Darío Fernández-Morera, The lyre and the oaten flute: Garcilaso and the pastoral. Tamesis Books, London, 1982; 128 pp. - Rivers, Elias L. (El Colegio de México, 1984)
Se reseñó el libro: The lyre and the oaten flute: Garcilaso and the pastoral.